The Voyage of the Rattletrap - Carruth, Hayden, 1862-1932; Wilder, Herbert Merrill, 1864- (Salt Lake City, UT : Project Gutenberg, 2005)
"The Voyage of the Rattletrap" by Hayden Carruth is a novel written in the late 19th century. The book narrates the adventurous journey of three boys$1 (BJack, the narrator, and his smaller friend Ollie$1 (Bas they embark on an exploratory venture in a prairie schooner. The story promises a mix of humor, camaraderie, and the trials of navigating the untamed landscapes of Dakota Territory. The opening of the book introduces us to the main characters and sets the stage for their adventure as they prepare to leave Prairie Flower. Jack and the narrator are eager to escape their mundane lives running a cheese factory and a printing office, respectively, and decide to set off on a voyage in a rickety wagon they affectionately name the "Rattletrap." They are soon joined by Ollie, Jack's young nephew, and a stray dog they name Snoozer. The boys enthusiastically plan their journey, discussing the supplies and preparations needed while also hinting at the challenges and whims of life on the prairie. As they depart, the onset of their adventure is marked by excitement and the promise of an unpredictable expedition filled with laughter and possible mishaps. (This is an automatically generated summary.)s
Release date is 2005-08-24
Produced by Cyril N. Alberga
Keywords: Dakota Territory -- Fiction